Academic identities research: mapping the field's theoretical frameworks. Issue 2 (23rd February 2022) - Barrow, Mark; Grant, Barbara; Xu, Linlin
ABSTRACT: For several decades, Western universities have been subject to wide-ranging structural, financial and ideological changes. These changes have problematised afresh the meaning of academic identity as evidenced by the emergence of a substantial, international, anglophone research literature. This article examines how the idea of academic identity has been theorised to date in a set of highly cited research literature, with the ambition of providing some points of departure for further work in the area. Our analysis of 11 works suggests a small set of related (constructivist) theories provides the core resources for academic identities scholarship, although somewhat varied understandings of agency and power/politics surface in the discussions and implications advanced by different authors. As a result of this analysis, we suggest the need to extend the theoretical and empirical scope of academic identity research if we are to produce new insights and ways forward.